An account of the history of biology in Costa Rica, in the voice of Dr. Rafael Lucas Rodríguez Caballero - Hilje Quirós, Luko (2023)
Half a century ago, in December 1972, came into light an account titled History of Biology in Costa Rica, by the eminent botanist Rafael Lucas Rodríguez Caballero. It corresponded to the written version of a lecture delivered for a seminar at the Centro Universitario Regional de San Ramón, University of Costa Rica. Thus far it has remained unknown since it was initially published as a booklet that was not widely disseminated. Nevertheless, it is of great value, as it represents the first synthesis about the history of biology in Costa Rica. Therefore, herewith it is rescued and transcribed in full, in addition to interpreting various aspects of its content through footnotes and including some pertinent illustrations.